Contexto petrográfico, caracterização e parâmetros petrológicos de óxidos de fe-ti das rochas metamáficas do setor nw do domínio Ceará central, província Borborema - Cavalcante, Dayme Hermesson Alves (2021)
The high pressure/temperature zones of Cariré and Forquilha are situated the west of the Tamboril-Santa Quitéria Complex, northwest portion of the Ceará Central Domain, NW Borborema Province, NE Brazil. This are formed by lenses of granulitic and metamafic rocks enclosed in metamorphosed metagranodiorites and metassediments in upper amphibolite and/or granulite facies. Textural and mineral re-equilibration relations in metamafic rocks determine a polymetamorphic history to both the zones. Decompression features (clinopyroxene + plagioclase ± hornblende symplectites and coronitic texture with plagioclase collar at garnet), from the retrograde metamorphism, highlight metamorphism in high-grade metamorphic conditions in the Carire Granulite Zone (CGZ) and Forquilha Eclogite Zone (FEZ). Farther, in the CGC is recorded possible metamorphic overprint process subsequent to main retrograde metamorphism, characterized texturally by the hornblende breakdown to clinopyroxene. Multiphase Fe-Ti oxides assemblage is identified in retrogressed mafic granulite from the ZGC, represented by ilmenite, titanomagnetite, rutile, spinel and hematite. In these metamafic rocks occur rutiles included in ilmenite host, associated to this inclusion texture exhibit titanomagnetite lamellar exsolution and they never coexist with magnetite. In late alteration stage exhibit hematite intergrowth, in the ilmenite host, that not coexists with rutile, and replacement of Fe-Ti oxides by titanite. In the FEZ, the Fe-Ti oxides present in retrograded eclogite are constituted by ilmenite, rutile and martitized magnetite. Have textural relation characterized by rutile inclusion in ilmenite grains, with late alteration to titanite. The average composition of coexisting rutile and ilmenite in retrogressed mafic granulite, indicate an oxygen fugacity of FMQ -2.75, whilst the retrograded eclogite are characterized by depletion of Fe3+ in the ilmenite the that did not allow estimate the logƒO2 by the use rutileilmenite oxybarometer.